Implementasi Penentuan Harga Pokok Produksi (HPP) dengan Metode Full Costing dan Pengoptimalan Pemasaran Digital pada Penjualan Snack Guparove Studi Kasus pada Pelaku UMKM Ibu Suwarsi Kelurahan Margomulyo - Rini Susilawati; Shafa Salsabila; Safitri Safitri; Dede Pebrianto (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
The aim of this research is to analyze implementation of determining the cost of goods produced (hpp) with the full costing method and optimizing digital marketing on the sale of guparove snacks case study on umkm actors ibu suwarsi kelurahan margomulyo. This research method uses the Steps method which was carried out for 4 months in Margo Mulyo village by group 7. Innovation Development (PI) activities carried out in the form of mentoring MSMEs (Micro, Small and Medium Enterprises), especially GUPAROVE MSMEs in RT 46 Margo Mulyo Village and conducting seminars, including marketing strategies, product innovation processing, packaging development, and training in recording or financial management through digital and manual. The seminar activity carried out, namely MSME Marketing Innovation Optimizing Social Media & Creative Content to Increase Sales and MSMEs in Margo Mulyo Village, aims to provide an understanding to MSME players and their surroundings about the importance of recording financial statements digitally for decision making and minimizing financial fraud. With this development, it is hoped that MSME players can reach wider marketing and further utilize digital applications to make more efficient financial reporting performance.